The relationship between profitability and financial liquidity among the importers of best-selling brands of new cars in poland - Paweł Łojek (Central European Economic Journal (CEEJ), 2020)
The automotive industry is a particularly sensitive sector of the economy. Numerous legal changes have been introduced in Poland that may affect the company's liquidity and profitability. Sales of new vehicles in Poland were very high until the end of 2019. I have presented the most recently available financial data, and hence it can be concluded that they are not distorted. The article discusses the issue of cash flow statements and the associated financial ratios, as well as assesses the financial liquidity among the importers of new, ten best-selling car makers in Poland between 2015 and 2019. Moreover, I have analysed the relationship between profitability ratios and liquidity ratios as well as cash adequacy ratios during this period. According to my findings, in most cases, there is a positive and strong relationship between profitability and financial liquidity in the automotive industry.
Keywords: G30; M40; 330; financial liquidity; automotive sector; cash flow statement; ratio analysis